2005
DOI: 10.3727/000000005783992070
|View full text |Cite
|
Sign up to set email alerts
|

Casein Kinase II Phosphorylation Regulates αNAC Subcellular Localization and Transcriptional Coactivating Activity

Abstract: The subcellular localization of the alphaNAC coactivator is regulated, but the signaling pathways controlling its nucleocytoplasmic shuttling and coactivation function are not completely characterized. We report here that casein kinase II (CK2) phosphorylated alphaNAC on several phosphoacceptor sites, especially in an amino-terminal cluster. Deletion or mutation of the clustered CK2 sites induced nuclear accumulation of alphaNAC in cells. alphaNAC also localized to the nucleus when endogenous CK2 activity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…Furthermore, in the CK2␣ screen, most of the binding partners found were CK2␤ (97.5% as determined by PCR screen), in line with previous work (20). In addition, in this screen, various proteins already known to interact with, or to be phosphorylated by, CK2, such as calmodulin (21) or ␣NAC (nascent-polypeptide associated complex alpha) (22) were also found. Taken together, these binding partners confirmed that the folding of the bait proteins in-fusion with GAL4 was comparable to that of the native protein.…”
Section: Ck2 Interacts With G␣s and G␣olfsupporting
confidence: 85%
“…Furthermore, in the CK2␣ screen, most of the binding partners found were CK2␤ (97.5% as determined by PCR screen), in line with previous work (20). In addition, in this screen, various proteins already known to interact with, or to be phosphorylated by, CK2, such as calmodulin (21) or ␣NAC (nascent-polypeptide associated complex alpha) (22) were also found. Taken together, these binding partners confirmed that the folding of the bait proteins in-fusion with GAL4 was comparable to that of the native protein.…”
Section: Ck2 Interacts With G␣s and G␣olfsupporting
confidence: 85%
“…1-3). Protein activity and subcellular localization are known to be regulated by phosphorylation (51)(52)(53)(54). We have repeatedly detected Htt Thr-3 phosphorylation by mass spectrometry and immunoblot analysis using a phospho-T3 specific antibody.…”
Section: Poly(q) Toxicity and Proteinmentioning
confidence: 96%
“…31 The protein kinases that could introduce this priming phosphoserine vary depending on the substrates, and GSK-3b and casein kinase II may be the candidates for aNAC. 46 However, at present, the aNAC protein does not fulfill all the requirements as a physiological substrate for GSK-3b. 27,28 Further studies are required for determining whether aNAC is a target of GSK-3b.…”
Section: Discussionmentioning
confidence: 99%